Características físico químicas de leche fresca, procedente de establos de la provincia de Trujillo, abril-mayo 2018 - MIranda López, Carlos Ausberto (2018)
The objective of the present work was to evaluate the physical and chemical characteristics of fresh milk, from four stables in the province of Trujillo, April-May 2018. Three samples of milk were used from each stall, immediately after milking. The results were compared with the standards established in the Peruvian Technical Standard for milk and milk products NTP 202.001: 2016 and the Practical Manual of Bromatology 2018. The organoleptic characteristics were determined. For the physical and chemical characterization, density, acidity, fat, proteins, lactose, total solids, non-fat solids and ash were determined. In the milk samples from stables 1 and 2, a low content of fat and proteins was found not complying with the NTP, which are related to a lower concentration of total solids, non-fat solids and a low density. To itself in the samples from stables 3 and 4, 100% of the tests carried out were found within the standards of the NTP and the Practical Manual of Bromatology 2018. It was determined that the samples of 50% of the stables studied, of the Province of Trujillo, comply with the established quality parameters